PENGARUH KINERJA KEUANGAN DAN KARAKTERISTIK DEWAN TERHADAP PENGUNGKAPAN KARBON (Studi Empiris Pada Perusahaan Sektor Non Finansial yang terdaftar di Bursa Efek Indonesia (BEI) 2018-2020) - Elga Pinka Arwangga; Surya Raharja (Diponegoro Journal of Accounting, 2023)
This study aims to determine the effect of profitability, growth, leverage, board size, board gender, and board independent disclosure of emission carbon in non-financial companies listed on the Indonesia Stock Exchange (IDX). This research uses a quantitative method. The sample used in this study is a non-financial company listed on the Indonesia Stock Exchange in 2018- 2020. The samples of this study used a purposive sampling method. The number of samples in this research are 127 taken from 39 companies.Data analysis uses multiple linear regression. The result of this analysis prove that profitability , board size, board gender, and board independent does not affect the disclosure of emission carbon. However, growth and leverage has a significant effect on the disclosure of emission carbon.